Sistem Informasi Penjualan Di Toko Sarana Pertanian Citra Lawu - Wahyudi, Eko, Dr. Ir. Bana Handaga, M.T (2015)
Inside the agriculture tools shop many of transaction data, goods stock, and other things that cannot be memorized. Even if this matter can be, impede the process of order stuff, if the stock being diminishes. On that score, the system is needed that can encode that data list with fixing in a data managing system. The fixes that will be doing are making with use registry system, which computerized, both in registry aspect and supply goods, the transaction registry and the other process that, connected dealt only with shop activity. This research made with the purposes to deliver the computerized basis system, and facilitate the employees in transaction recording. In this research is made application for a store selling agriculture using the programming language Java with NetBeans IDE and MySQL. Thesis research in order to place this in Citra Lawu agriculture tools shop that places in Mener orchard, Segorogunung village, Ngargoyoso sub district, Karanganyar regency. The development method that used in this research is SDLC system (System Development Life Cycle). Data required in the manufacture sales information system, which includes the type of goods, quantity of goods, prices of goods and other data you need. In experiments it was concluded the following applications: 1) Success to make the sales system application on java desktop basis. 2) This sales system application helps on sales transaction record in Citra Lawu Agriculture Tools Shop. 3) This system also equipped with login, and every user has an access right which, different as the position they're have. 4) As follow the questioner data result that it got the screen design good enough, easy to use, the features is completely enough, the users quietly satisfied on operation it, and with the scoring all of this application is quiet ones.